Granulocyte colony stimulating factor in neutropenic patients with infective endocarditis. Issue 1 (1st January 1998) - Borgbjerg, Birgitte Molke; Hovgaard, Doris; Laursen, Jørn Bech; Aldershvile, Jan
Abstract : A well known complication in the treatment of infectious endocarditis is development of neutropenia caused by treatment with antibiotics in high concentrations over long periods. Neutropenia often necessitates discontinuation of antibiotic treatment. Three patients with infectious endocarditis who developed neutropenia are reported. The patients were treated with granulocyte colony stimulating factor (G-CSF), a haematopoietic growth factor that stimulates neutrophils. G-CSF induced an immediate increase in white blood cell count, primarily neutrophils. G-CSF may be effective in ameliorating neutropenia in patients who receive antibiotics for treatment of infectious endocarditis.